Craving Homes in Ila Arab Mehta’s Fence - Joby, Metty (Muslim English Literature, 2023)
Owning a home has always been a dream for every individual, and one’s life savings are invested in possessing a home, especially in the Indian context. Indian novelists have portrayed how their characters strive to build a ‘home’ for themselves, thereby asserting their identity. The present study explores the protagonist Fateema’s dire desire to own a house of her own in a mixed ghetto wherein people from different religions live together in peace and harmony. This elusive utopian thought is depicted poignantly in Ila Arab Mehta’s novel Fence. The cultural constructs in the Gujarati society described in the novel and the hegemonic influence portrayed in the novel are explored through the experiences of various characters. The food, clothing, language, and mannerisms of the Muslim society, as compared to the majority community in Gujarat of the late twentieth century, are portrayed in the novel as only cultural constructs leading to the subjugation of the Muslim community. Hence, an attempt is being made to study the novel Fence from the perspective of cultural studies and calls for a broader outlook in encapsulating everyone within a multicultural framework, strengthening the social fabric.